Clinical and histopathological responses to bee venom phonophoresis in treating venous and diabetic ulcers: a single-blind randomized controlled trial - Othman, Eman M.; Hamada, Hamada Ahmed; Mohamed, Ghada I.; Abdallah, Ghada A.; Ahmed, Zeinab S.; Al-Shenqiti, Abdullah M.; Kadry, Ahmed Mahmoud (Frontiers in Medicine, 2023)
Abstract The conducted study was to evaluate the efficacy of bee venom (BV) phonophoresis on the healing of chronic unhealed venous and/or diabetic foot ulcers Also, for comparing the healing rate of diabetic and venous ulcers. One hundred patients (71 males and 29 females) with an age range of 40 to 60 years’ old who had chronic unhealed venous leg ulcers of grade I, grade II, or diabetic foot ulcers with type II diabetes mellitus participated in this study. They randomly assigned into four equal groups of 25: Group A (chronic venous ulcer group) and group B (diabetic foot ulcer group) who both received conservative treatment of medical ulcer care and phonophoresis with BV gel, in addition to group C (Control group for group A) and group D (Control group for group B) who both received conservative treatment of medical ulcer care and received sham ultrasound sessions only without BV gel. Wound surface area (WSA) and ulcer volume measurement (UVM) was used to assess the ulcer healing pre-application (P0), post-6 weeks of treatment (P1), and after 12 weeks of treatment (P2). In addition to Ki-67 immunohistochemistry to evaluate the cell proliferative in the granulation tissue of ulcers pre-application (P0) and after 12 weeks of treatment (P2) for the 4 groups. This research revealed a statistical significance improvement (p ≤0.05) in the WSA, and UVM with no significant difference between study groups after treatment. Regarding Ki-67 immunohistochemistry showed higher post treatment values in the diabetic foot ulcer group in comparison to the venous ulcer group. Bee venom (BV) provided by phonophoresis is effective in accelerating venous and diabetic foot ulcer healing with higher proliferative effect on diabetic foot ulcer